Topological cyclodextrin nanoparticles as crosslinkers for self-healing tough hydrogels as strain sensors. (15th July 2021) - Chen, Junmin; Xu, Xiubin; Liu, Mingzhu; Li, Yunlong; Yu, Danfeng; Lu, Yu; Xiong, Meiting; Wyman, Ian; Xu, Xuefeng; Wu, Xu
Highlights: Novel topological nanoparticles (TNPs) were developed as crosslinkers. Novel TNPs-crosslinked hydrogels were successfully prepared via facile preparation. The hydrogels showed excellent mechanical and readily recycle performance. The hydrogels could serve as flexible strain sensors to monitor human activities. The sensors showed good fatigue resistance, sensitivity and a wide sensing range of 0–1800 %. Abstract: Hydrogels have been widely used for various applications, and thus addressing the challenges associated with the design of sustainable hydrogels has become an important issue. However, little attention has been devoted toward the design of crosslinkers which are often toxic, lack self-healing capabilities, and derived from petrochemicals. Herein, novel cyclodextrin topological nanoparticles (TNPs) have been constructed. These TNPs were found to possess crosslinking capabilities and the corresponding TNPs-crosslinked hydrogels showed excellent mechanical performances with a high stretchability of 1860 % and stress of 180 kPa and good anti-fatigue abilities. These hydrogels could be readily recycled and used for modular assembly and disassembly in various shapes and could serve as flexible strain sensors to monitor human activities with a sensing range of 0–1800 %, controllable sensitivity, and good fatigue resistance. These topological nanoparticles can inspire the design of novel physical crosslinkers for novel flexible strain sensors, tough and self-healing hydrogels, and soft robotics.